The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1029/2018jc013884
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Variability of Conditions Favoring an Iron‐Induced Diatom Bloom Downstream of the Kerguelen Plateau

Abstract: Heterogeneity in phytoplankton distribution is related to spatial and temporal variations in biogeochemical and ecological processes. In the open ocean, the interaction of these processes with meso‐ and submeso‐scale dynamics (1‐100 km, few days to months) gives rise to complex spatio‐temporal patterns, whose characterization is difficult without extensive sampling efforts. In this study, we integrate pigment sampling and multisatellite data to assess the link between iron enrichment and diatom dominance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…However, latitudinal movements and variation of frontal positions and associated meandering and eddy shedding, particularly within the Polar Frontal Zone (PFZ), facilitate cross-frontal exchanges (Lutjeharms and Baker, 1980;Bryden, 1983;Heywood et al, 1985;Lutjeharms et al, 1985;Pakhomov et al, 1997;Chiba et al, 2001;Hunt et al, 2001Hunt et al, , 2002Bernard et al, 2007;Foppert et al, 2017). Eddies that drift some distance from their origin provide an effective means of transporting faunas into different water masses (Atkinson et al, 1990;Bernard et al, 2007) and can enhance zooplankton productivity and abundance, particularly at their peripheries (Bernard et al, 2007;Della Penna et al, 2018). Planktonic larvae of benthic species can cross such frontal zones in eddies (Clarke et al, 2005), and also have new and increasing passive opportunities on floating debris such as plastic (Barnes, 2002;Horton and Barnes, 2020).…”
Section: Passive Dispersalmentioning
confidence: 99%
“…However, latitudinal movements and variation of frontal positions and associated meandering and eddy shedding, particularly within the Polar Frontal Zone (PFZ), facilitate cross-frontal exchanges (Lutjeharms and Baker, 1980;Bryden, 1983;Heywood et al, 1985;Lutjeharms et al, 1985;Pakhomov et al, 1997;Chiba et al, 2001;Hunt et al, 2001Hunt et al, , 2002Bernard et al, 2007;Foppert et al, 2017). Eddies that drift some distance from their origin provide an effective means of transporting faunas into different water masses (Atkinson et al, 1990;Bernard et al, 2007) and can enhance zooplankton productivity and abundance, particularly at their peripheries (Bernard et al, 2007;Della Penna et al, 2018). Planktonic larvae of benthic species can cross such frontal zones in eddies (Clarke et al, 2005), and also have new and increasing passive opportunities on floating debris such as plastic (Barnes, 2002;Horton and Barnes, 2020).…”
Section: Passive Dispersalmentioning
confidence: 99%
“…As chain-forming and large-diatom blooms occur during relatively short periods, it has been hypothesized that smallsize cells are an essential element of Antarctic food webs, especially during winter and periods preceding blooms (Detmer and Bathmann 1997). Satellite data and sampling has indicated that phytoplankton communities on the plateau switch to an ecosystem dominated by small phytoplankton before (Rembauville et al 2017), and also likely, after the bloom (Penna et al 2018). As such, the plateau of Kerguelen could also include a persistent and functionally important small phytoplankton community, on which diatom blooms superimpose themselves (Smetacek et al 1990).…”
mentioning
confidence: 99%
“…This area is far away from terrestrial iron sources and the influence of sea ice (Bowie et al, 2009;Cavalieri et al, 1996;Lannuzel et al, 2011), suggesting that these eddies are produced without iron input from any islands (Moreau et al, 2017). This is in contrast to the situation where high chlorophyll eddies observed near islands like the Kerguelen Plateau, have productivity that is likely enhanced by terrestrial iron (Della-Penna et al, 2018;Grenier et al, 2015).…”
Section: Biomass Distribution and Relationship With Eddies And Fronta...mentioning
confidence: 98%